2015
DOI: 10.1515/reveh-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Increased mercury release from dental amalgam restorations after exposure to electromagnetic fields as a potential hazard for hypersensitive people and pregnant women

Abstract: AbstractOver the past decades, the use of common sources of electromagnetic fields such as Wi-Fi routers and mobile phones has been increased enormously all over the world. There is ongoing concern that exposure to electromagnetic fields can lead to adverse health effects. It has recently been shown that even low doses of mercury are capable of causing toxicity. Therefore, efforts are initiated to phase down or eliminate the use of mercury amalgam in dental restorations. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…subjects although the difference was not statistically significant. these results were the same found in other studies that reported no statistical significance found between dental staff either exposed or non-exposed to amalgam [15][16][17][18]. Interestingly, the study found measurable amount of mercury concentrations in both hair and nail of control subjects with and without amalgam restorations (2.04 µg/l, 1.5 µg/l, 1.9 µg/l and 1.6 µg/l respectively) most probably due to environmental exposures and dietary habits.…”
Section: Resultssupporting
confidence: 93%
“…subjects although the difference was not statistically significant. these results were the same found in other studies that reported no statistical significance found between dental staff either exposed or non-exposed to amalgam [15][16][17][18]. Interestingly, the study found measurable amount of mercury concentrations in both hair and nail of control subjects with and without amalgam restorations (2.04 µg/l, 1.5 µg/l, 1.9 µg/l and 1.6 µg/l respectively) most probably due to environmental exposures and dietary habits.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, current findings should be corroborated in future studies assessing other aspects of Hg toxicity from the dental amalgam. For example, the relatively new data about an increased mercury release after exposure to electromagnetic fields (as those generated by mobile phones or MRI) [36,39]. Identifying them is a major challenge and worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kursun et al have reported that exposure to X-rays, an ionizing component of the broad spectrum of electromagnetic radiation, can increase the mercury release from dental amalgam restorations 4 . These findings have recently been reviewed by Mortazavi and Mortazavi 5 . As a shortcoming of the study conducted by Lygre et al, these researchers have not considered the issue of the release of mercury from dental amalgam restorations after exposure to EMFs.…”
Section: Dear Editormentioning
confidence: 91%